Exploration of the viticultural potential of borojó (Borojoa patinoi Cuatrec.): Feasibility study for fruit wine production - villa Ramirez, Rigoberto
Borojó (Borojoa patinoi Cuatrec.) Is an arboreal species belonging to the Rubiaceae family, which grows mainly in Colombia, and Ecuador, especially in humid forest areas and adapts to heights of up to 1200 m; the fruit is fleshy with high nutritional value that positions it as a promising resource, it is used to prepare preserves and wine, but its main use is as a refreshing drink with possibilities for its transformation. In the Postharvest Research Laboratory of the University of Quindío, two trials were carried out for the production of fruit wine, where concentrations of 10% and 20% borojó pulp were analyzed, and physicochemical and microbiological tests were carried out. The physicochemical characterization for the two treatments showed an alcohol content of 12.5% ​​for treatment 1 and 10.3% for treatment 2. These results are within the established parameters (Colombian technical standard 708 alcoholic drinks fruit wines), likewise; the microbiological analyzes showed results within the permitted range for the borojó and wine pulp (Norma Técnica Colombiana NTC 404). (nmp <3 and 4,000-4,450 cfu / g, Coliforms and mesophiles, respectively, (1,260 -1,700 cfu / g) for molds and yeasts